2004
DOI: 10.1143/jjap.43.4351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sputtered High-Energy Particles on the Structure and Photocatalytic Performance of TiO2 Films Prepared by a DC Reactive Sputtering Method

Abstract: By using the Kevin–Meyer formula, we calculated the energy of the high-energy particles (recoil argon ions and negative oxygen ions) that are unique to sputtered thin-film formation when they arrived at a substrate during the sputtering process. We found that the energy of the high-energy particles arriving at the substrate decrease if total gas pressure increases, whereas the photocatalytic performance of a TiO2 film increases if the total gas pressure increases. We also found that as total gas pressure incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…While on the other hand, the index for glass substrate was 1.6 [μmol l − 1 min − 1 ]. These results indicate that our films, deposited at such a high deposition rate, have similar MB decomposition performance to that of films obtained using reactive sputtering method [15][16][17].…”
Section: Photocatalytic Characteristicssupporting
confidence: 76%
“…While on the other hand, the index for glass substrate was 1.6 [μmol l − 1 min − 1 ]. These results indicate that our films, deposited at such a high deposition rate, have similar MB decomposition performance to that of films obtained using reactive sputtering method [15][16][17].…”
Section: Photocatalytic Characteristicssupporting
confidence: 76%
“…2(d)) the energy of the sputtered high-energy particles is again several times lower than for the 10 Pa sample. This can be estimated by the Kevin-Meyer formula [11,12]. Noguchi et al reported that if the gas pressure increases the energy of the high-energy particles arriving at the substrate decreases and the surface morphology of TiO 2 films changes from a gap-free structure to a porous structure.…”
Section: Microstructurementioning
confidence: 99%
“…TiO 2 thin films were fabricated by DC reactive magnetron sputtering using parameters with which we had already successfully obtained highly reactive photocatalytic characteristics, as reported previously. 14,15) Shigesato's group has also reported on the use of reactive sputtering to deposit TiO 2 thin films. 16,17) They succeeded in fabricating highly reactive photocatalytic thin films by sputtering under a wide range of conditions, including differing intensities and shapes of magnetic field.…”
Section: Methodsmentioning
confidence: 99%